Osteolytic Lesion in the skullcap – Revealing Metastasis of a Thyroid Carcinoma - Tavares, Vanessa; Trancas, C; Campo, M; Santos, S (Citotech Online - Case Review, 2020)
Metastasis of thyroid carcinoma comprise a low percentage of the total observed in the skullcap. We present a case of a 72-year-old female patient with an osteolytic lesion on the right frontal skullcap, subjected to a fine needle aspiration, whose diagnosis suggested thyroid tissue. On the thyroid ultrasound, a detected nodule was punctured, as well as the osteolytic lesion, whose cellular characteristics were similar, classifying the lesion as a follicular tumor. The patient underwent a total thyroidectomy, and her histological diagnosis was Follicular Carcinoma.